Dynamic Sliding Mode Control of Ship Rudder-fin Joint Nonlinear System - Han Yao zhen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to realize good track keeping and roll reduction of the ship while navigating. A multiple input multiple output rudder-fin control system based on dynamic sliding mode algorithm is proposed. Rudder-fin joint system nonlinear mathematical model is established. Because the designed sliding mode controller makes sliding variables and the derivatives be zero, so it is essentially continous and overcomes traditional sliding mode chattering problem. Simulation results show that while keeping the command  track angle the designed control system can make the average roll angle about ±2°and realize good stabilization effect.